Speech Act in the Song Fateh by Vanguard and Doyz as a Medium of Social Criticism - Kinanti Dwiqalsa Paundrianagari; Adip Arifin (English Language Education Department, Universitas Majalengka, 2025)
This study analyzes the song Fateh by Morgue Vanguard and Doyz as a medium of social criticism using John Searle’s speech act theory. The song emerged amidst the Indonesian student protests in 2024, opposing the revision of the Regional Election Law, which was perceived as reinforcing oligarchy. The analysis of Fateh's lyrics identifies 42 lines categorized into five types of speech acts: representative acts (18 lines), directive acts (9 lines), expressive acts (6 lines), commissive acts (5 lines), and declarative acts (4 lines). Representative acts depict social realities of injustice, while directive acts call listeners to engage in collective action. Expressive acts convey emotions of anger and frustration, commissive acts reflect commitment to ongoing resistance, and declarative acts assert the social changes needed. The findings reveal that Fateh serves not only as a critique of social inequality but also as a tool for building solidarity and encouraging change through collective action.